Planar elongated B12 structure in M3B12 clusters (M = Cu-Au) - Solar Encinas, José.; Vásquez Espinal, Alejandro.; Leyva Parra, Luis.; Yáñez Osses, Osvaldo Andrés.; Inostroza, Diego; Valenzuela, Maria Luisa; Orellana, Walter; Tiznado, William (MDPI, 2023)
Here, it is shown that the M3B12 (M = Cu-Au) clusters’ global minima consist of an elongated planar B12 fragment connected by an in-plane linear M3 fragment. This result is striking since this B12 planar structure is not favored in the bare cluster, nor when one or two metals are added. The minimum energy structures were revealed by screening the potential energy surface using genetic algorithms and density functional theory calculations. Chemical bonding analysis shows that the strong electrostatic interactions with the metal compensate for the high energy spent in the M3 and B12 fragment distortion. Furthermore, metals participate in the delocalized π-bonds, which infers an aromatic character to these species.
Keywords: Aromaticity; Boron clusters; DFT computations; Group 11 metals; Enlaces químicos; Superficies de energía potencial